PENGARUH CORPORATE SOCIAL RESPONISBILITY, ENTERPRISE RISK MANAGEMENT DAN KARAKTERISTIK DEWAN DIREKSI TERHADAP RELEVANSI NILAI - Carla Josephine; Hasnawati Zainal (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
This study aims to determine the effect of corporate social responsibility, enterprise risk management, and the characteristics of the board of directors on value relevance. The characteristics of the board of directors are broken down into two more variables, namely the proportion of female directors and the education level of the CEO. The value relevance proxy are measured by combining the ratio of price book value and earnings per share. The sample was selected using a purposive sampling method, which resulted in 40 companies in the consumer goods industry included in the Indonesia Stock Exchange for the period 2017-2020. This study uses multiple linear regression analysis which is processed using SPSS 23. The results of the analysis show that the corporate social responsibility variable, the proportion of female director and the CEO's education level have a positive influence on value relevance while the enterprise risk management variable has no effect on value relevance.